Venous hemogasometry and blood electrolytes in Mangalarga Marchador mares submitted to aerobic training - Tiago Resende Garcia; Adalgiza Souza Carneiro de Rezende; Juliano Martins Santiago; Fernando Queiroz de Almeida; Mayara Gonçalves Fonseca; Ana Munõz (Ciência e Agrotecnologia, 2013)
The Mangalarga Marchador (MM) breed, valued for its marcha pace, has been excelling in functional activities such as marcha course. Considering the lack of information about sports physiology of the marcha horses, the development of training protocols and physical testing becomes essential and, in this context, the concentrations of blood gases and electrolytes provide additional information for the monitoring of metabolic changes induced by exercise. The goal of the study was to assess the hemogasometric responses and blood electrolyte concentration in MM mares during maximal effort treadmill tests carried out before and after training (trial 1) and between a maximal effort treadmill test and an incremental field test (trial 2). The trials assessed plasma lactate concentration, blood pH, oxygen and carbon dioxide blood pressures, and blood concentrations of the ions bicarbonate, sodium (Na+), potassium (K+), and calcium (Ca++). The study followed a randomized block in a split-plot design. In the first trial, the distances walked by the equines in the tests before and after training caused decrease (p<0.05) in pH and Ca++ concentration and increase in the concentrations of K+ and Na+. In the second trial, the influence of the type of test and the ambient temperature caused decrease (p<0.05) in pH and increase in the concentrations of K+ and Ca++. After training, MM mares had greater changes in pH and electrolyte concentrations.